Organizational communication : emprowerment in a technological society - Andrews, Patricia Hayes. (Houghton Mifflin, 1996)
Organizational communication in a technological age. Foundations of organization theory. Empowering employees through human resources management. Human relationships and interpersonal communication. Organizational design. Organizational leadership in the information age...